Potential of Pistachio-Hard Shell Based Thiosemicarbazone-Acetophenone for Pb2+Metal Sorption: Kinetic Studies, Isotherms Modeling and Optimization - Salih, Shameran Jamal; Faraj, Rezhna Hassan (Sulaimani Journal for Pure and Applied Sciences, 2017)
The batch studies conducted in the present work provide significant information regarding the adsorption of Pb2+ onto Pistachio-Hard shell-grafted-Thiosemicarbazone acetophenone. The sorption kinetics, isotherms and thermodynamics of Pb2+ onto adsorbent surface modified thiosemicarbazone acetophenone has been assessed under various operation conditions such as contact time, initial concentration of Pb2+, pH of the solution, temperature and adsorbent dosage. The FT-IR results of Pistachio-Hard shell -grafted-Thiosemicarbazone acetophenone showed that biomass has different functional groups and these functional groups are able to graft with Pb2+ in aqueous solution. The removal process reached maximum which was 97.08%. Equilibrium data fitted well with Freundlich isotherm model (1/n<1). Also, Kinetic data were best described by the pseudo-second order model. Thermodynamic studies showed that sorption of Pb2+ions were endothermic, spontaneous, and feasible. Finally, the optimum dosage of the modified adsorbent was 0.165g for adsorption process at pH 5.
Keywords: Schiff base; Adsorption Kinetics; Optimization; Removal